The redistributive effects of political reservation for minorities: evidence from India - Aimee Chin; Nishith Prakash (Institute for the Study of Labor (IZA), 2009)
We examine the impact of political reservation for disadvantaged minority groups on poverty. To address the concern that political reservation is endogenous in the relationship between poverty and reservation, we take advantage of the state-time variation in reservation in state legislative assemblies in India that arises from national policies that cause reservations to be revised and the time lags with which the revised reservations are implemented due to the timing of state elections. Using data on sixteen major Indian states for the period 1960-1992, we find that increasing the share of seats reserved for Scheduled Tribes significantly reduces poverty while increasing the share of seats reserved for Scheduled Castes has no impact on poverty. Political reservation for Scheduled Tribes has a greater effect on rural poverty than urban poverty, and appears to benefit people near the poverty line as well as those far below it.
Keywords: I38; J15; J78; 330; Affirmative action; poverty; minorities; India; Minderheitenpolitik; Arbeitsmarktdiskriminierung; Verteilungswirkung; Armutspolitik; Indien